Public Perception of the Influence of Money Politics in the 2024 General Election in Tangkobu Village, Paguyaman District, Boalemo Regency - Nurhaliza Lapinji; Ramli Mahmud; Saleh Al Hamid (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research aims to examine public perceptions of the influence of money politics during the 2024 General Elections (Pemilu) in Tangkobu Village, Paguyaman Subdistrict, Boalemo Regency. Money politics is a recurring phenomenon in Indonesia's democratic processes, particularly during elections. Such practices can influence voter preferences and undermine the integrity of elections that are meant to be fair and honest. This research employs a qualitative approach, with data collected through observation, in-depth interviews, and documentation. The informants include eligible voters, community leaders, and village-level election organizers in Tangkobu Village. The findings reveal that most community members are aware of the occurrence of money politics in the 2024 General Elections and perceive it as commonplace or even culturally ingrained, despite recognizing its detrimental effects on the quality of democracy. The main contributing factors to the public's acceptance of money politics include economic vulnerability, low levels of political education, and weak law enforcement. These findings suggest the need for improved political education, as well as stronger oversight and enforcement mechanisms to reduce money politics in future elections.